Analisis Perkembangan Produk dan Layanan Bank Syariah Di Pakistan - Tri Wina Sabrina; Mey Yunanda; Ahyarul Juanda Sagala; Khaidar Rahmaini Jamila (Jurnal Perbankan Syariah, 2025)
Islamic banking in Pakistan has unique characteristics compared to other Muslim countries, as from its early development it was directed toward the Islamization of the entire national banking system. This study aims to analyze the development of Islamic banking products and services in Pakistan as well as the dynamics accompanying it. The research method employed is a descriptive qualitative approach through a literature review, utilizing secondary data obtained from books, scholarly articles, and relevant reports. The results indicate that Islamic banking in Pakistan has experienced significant growth, as reflected in the diversification of financing products such as murabahah, mudarabah, musharakah, and ijarah, as well as savings and investment services and Islamic financial instruments such as sukuk. In addition to functioning as commercial financial institutions, Islamic banks in Pakistan also perform a social role through the management of zakat, waqf, and Islamic social funds. Regulatory support from the State Bank of Pakistan has further contributed to the growth of this sector. Nevertheless, this development continues to face challenges, including limited Islamic financial literacy, the need for product innovation, and competition with conventional banks. This study is expected to contribute to the enrichment of academic literature on Islamic banking and to serve as a reference for the sustainable development of the Islamic banking industry in Pakistan.